Molecular Weight and Structural Properties of Biodegradable PLA Synthesized with Different Catalysts by Direct Melt Polycondensation - Lee, Hyung Woo; Insyani, Rizki; Prasetyo, Daniel; Prajitno, Hermawan; Sitompul, Johnner P. (Journal of Engineering and Technological Sciences, 2015)
Production of biodegradable polylactic acidÂ  (PLA)Â  from biomassbased lactic acid is widely studied for substituting petro-based plasticsÂ  or polymers. This study investigated PLA production from commercial lactic acid in a batch reactor by applying a direct melt polycondensation method with two kinds of catalyst,Â  Î³-aluminium(III)Â  oxideÂ  (Î³-Al2O3) orÂ  zinc oxide (ZnO),Â  in reduced pressure. The molecular weight of the synthesized PLA was determined by capillary viscometry and its structural properties were analyzed by functional group analysis using FT-IR. The yields of polymer production with respect to the theoretical conversion were 47% for Î³-Al2O3 and 35% for ZnO. However, the PLA from ZnO had a higher molecular weight (150,600 g/mol) than that from Î³-Al2O3 (81,400 g/mol). The IR spectra of the synthesized PLA from both catalysts using polycondensation show the same behavior of absorption peaks at wave numbers from 4,500 cm-1 to 500 cm-1, whereas the PLA produced by two other polymerization methods â polycondensation and ring opening polymerization âshowed a significant difference in % transmittance intensity pattern as well as peak area absorption at a wave number of 3,500 cm-1 as âOH vibration peak and at 1,750 cm-1 as âC=O carbonyl vibrational peak.